The Effect of Bibliotherapy in Teeth-brushing Behavior to Prevent Dental Caries Among Pre-School Children - Rizqi Nursasmita; Rahayu, Putri; Argarini, Diah (International Journal of Midwifery and Health Sciences, 2023)
Background: Dental caries is a dental disease caused by the presence of food residue and bacteria for a long time, where the bacteria produce acid which can cause tooth decay. In order for preschool-aged children to prevent tooth decay, bibliotherapy is needed which can provide insight and change the behavior of preschoolers. Bibliotherapy is using a story to start a discussion about a problem and it should be used as an alternative to problem solving. Purpose: To determine the effect of bibliotherapy on tooth brushing behavior for the prevention of dental caries in preschool children at one of kindergarten in South Jakarta, Indonesia. Method: This study used quasi-experimental design with pre-test and post-test design, where the intervention group is measured or observed before and after the intervention. The research sample consisted of 30 respondents. The sampling technique uses total sampling. The research instrument is a tooth-brushing behavior questionnaire. Data analysis used the Wilcoxon test to determine the effect of bibliotherapy on tooth-brushing behavior. Results: The behavior of the respondents before the intervention showed that the behavioral variable with good category was 13.3% and after the intervention showed that the variable with good behavior increased to 96.7%. The results of the study obtained a p value of 0.000 <0.05 which indicates that bibliotherapy has an effect on tooth-brushing behavior. Conclusion: There is an effect of bibliotherapy on tooth-brushing behavior to prevent dental caries in preschool children in one of kindergarten in South Jakarta.